Effect of two-only-meal frequency and exercise on HbA1C outcomes, weight, and anti-diabetic medication in type 2 diabetes in a popular lifestyle change campaign in Maharashtra, compared to conventional clinical management: A quasi-experimental multicenter study in Maharashtra - Shyam Ashtekar; Pradeep Pradeep Deshmukh; Nitin Ghaisas; Chandrashekhar Ashtekar; Sameeran Upasani; Madhuri Kirloskar; Ajit Kumthekar; Mrunalini Bharat Kelkar; Ratna Ashtekar; Parag Misar; Vikas Ratnaparakhe; Manjiri Dhamangaonkar; et al. (Indian Journal of Community Medicine, 2023)
Background: Rising prevalence and poor outcomes make the twin challenges of diabetes epidemiology. This study evaluates effect of 2-only-daily-meals with exercise (2-OMEX) for its effect on HbA1c, oral hypoglycaemic agents (OHA) usage, body-weight among type-2-diabetes (T2DM) subjects, compared with conventional management. Material and Methods: A quasi-experimental, multicentre study in 2-OMEX arm, and HbA1c by HPLC method. HbA1c and body-weight changes were analyzed by 'Difference in Difference' (DID) method. Meal frequency, exercise, energy intakes were based on recall. The required sample size was 20X2 for 1.1 difference in HbA1c with 95% CL and 80% power Results: Socio-demographic and risk profile of analysed and omitted subjects were similar. Studied arms were also similar in baseline features. The results in 2-OMEX and conventional arm are: complete records analyzed 201 and 120. Mean (sd) values as follows: observation days 234 and 236, age 52.03(8.84) and 52.45(9.48) years (P=0.6977), diabetes duration 4.6(3.05) and 4.9(2.97) years, BMI 27.28(5.27), 26.90(3.74) (P = 0.1859), baseline HbA1c gm% 7.46(1.52) and 7.55(1.58), end-line proportion of subjects attaining HbA1c ≤6.5gm% was 35.3% and 19.2% (P=0.002), bodyweight loss 2.57% and 1.26%. OHA count 1.6 (1.23) and 2.7(1.06), (P=0.0003). In 2-OMEX arm log-normal HbA1c declined significantly by 0.94 (95%CI: 1.60 to – 0.56, p=0.0333), weight loss difference 0.96 kg, and statistically not significant (P=0.595). Two subjects in 2-OMEX arm showed partial remission. Mean baseline Kcal intakes in 2-OMEX arm, were 1200.4(F) and 1437.3(M) were significantly higher than conventional arm (F) and 1430 (M) Conclusion: The 2-OMEX showed a sizeable and significant reduction in HbA1c and OHA use, in 7-months, with moderate intakes, compared to the conventional arm, possibly attributable to fewer insulin surges. More studies are required for its impact and pathways.